2012
DOI: 10.1167/iovs.12-9935
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Murine Experimental Autoimmune Optic Neuritis by Mature Dendritic Cells Transfected with Calcitonin Gene-Related Peptide Gene

Abstract: PURPOSE. Calcitonin gene-related peptide (CGRP) exhibits prominent anti-inflammatory actions. We examined whether CGRP-transfected dendritic cells (DC) prevent the development of experimental autoimmune optic neuritis (EAON) and experimental autoimmune encephalomyelitis (EAE). METHODS.A human CGRP-expressing plasmid was constructed, and used to transfect C57BL/6 mouse bone marrow-derived matured DC (mDC) by electroporation methods. Transfection efficiency was 50% with 80% cell viability. C57BL/6 mice were immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…There was no difference between these two groups (Figure S1). This result is in agreement with results described in the literature [25]. Depending on experimental design, the pumps were implanted either immediately after, 14 days after, or 14 days before the first injection of MOG.…”
Section: Methodssupporting
confidence: 92%
“…There was no difference between these two groups (Figure S1). This result is in agreement with results described in the literature [25]. Depending on experimental design, the pumps were implanted either immediately after, 14 days after, or 14 days before the first injection of MOG.…”
Section: Methodssupporting
confidence: 92%
“…Very recently, Matsuda et al (2012) showed that i.v. injection of dendritic cells transfected with CGRP reduced EAE development.…”
Section: Discussionmentioning
confidence: 99%
“…This has since been corroborated in models of psoriasis where TH17 cells are the dominant inflammatory phenotype (Ostrowski et al, 2011). In contrast, the association of CGRP with CD4+CD25+Foxp3+ cells has also been studied in a model of EAE (Matsuda et al, 2012). CGRP transfected DCs were able to increase differentiation of CD4+CD25+Foxp3+ regulatory cells (Matsuda et al, 2012).…”
Section: Cgrp Regulates Lymphocyte Differentiation and Cytokine Produmentioning
confidence: 99%
“…In contrast, the association of CGRP with CD4+CD25+Foxp3+ cells has also been studied in a model of EAE (Matsuda et al, 2012). CGRP transfected DCs were able to increase differentiation of CD4+CD25+Foxp3+ regulatory cells (Matsuda et al, 2012). CGRP, is also produced by B lymphocytes in inflammatory conditions under the influence of nerve growth factor (NGF) (Bracci-Laudiero et al, 2002).…”
Section: Cgrp Regulates Lymphocyte Differentiation and Cytokine Produmentioning
confidence: 99%